Genetic variability of Leishmania infantum in naturally infected dogs in the state of Bahia, Brazil - Fábio Santos Carvalho; George Rêgo Albuquerque; Paulo Luiz Souza Carneiro; Amauri Arias Wenceslau (Revista Brasileira de Parasitologia Veterinária)
Abstract In Brazil, Leishmania infantum mainly affects humans and dogs. The state of Bahia presents many dogs that are positive for this parasite. Despite the importance of epidemiology in this region, there are still very few studies that have assessed the genetic characteristics of L. infantum. The aim of this study is to investigate the genetic variability of L. infantum isolated identified in naturally infected dogs, in order to verify occurrence of subpopulation of this parasite in the different biomes existing in the state of Bahia. Thirty-two samples of L. infantum were analyzed, which were obtained isolated in dogs from the Mata Atlântica (rainforest), Caatinga (semi-arid scrub forest), and Cerrado (a vast tropical savannah eco-region) Bahia municipalities’ biomes. All animals presented with clinical changes suggestive of Leishmania spp. and they exhibited positive reactions to serological tests. kDNA analysis with RFLP markers revealed the presence of genetic variability and gene flow in subpopulations of L. infantum; samples from the Mata Atlântica areas were genetically more similar to those from the areas of Caatinga and they were less likely to resemble those of the Cerrado. This data may be used to investigate the dissemination of parasite in the canine population of state of Bahia.